Effects of chronic psychological stress on testicular cell senescence in rats and role of glucocorticoid receptor in the process - YANG Binwei; YANG Binwei; SUN Lei; LING Xi (陆军军医大学学报)
Objective To investigate the effect of chronic psychological stress on testicular cell senescence in rats and the role of glucocorticoid receptor (GR) in the process. Methods Thirty-two male SD rats (4~6 weeks old, weighing 120~140 g) were randomly assigned into dimethyl sulfoxide (DMSO) group, mifepristone (RU486) group, chronic unpredictable mild stress (CUMS) group, and CUMS+RU486 group.DMSO of 0.5 ml/(kg·d) was injected subcutaneously into the rats of DMSO group.After the rats of the CUMS group were exposed to CUMS, mifepristone of 1 mg/(kg·d) was given to the rats of the RU486 group and CUMS+RU486 group.All the above 4 groups were inflicted for 42 consecutive days.After modeling, the psychological stress status of rats was evaluated with animal behavioral experiments.Computer-aided sperm analysis (CASA) system was used to detect sperm density.ELISA was employed to measure the serum levels of corticosterone (CORT), sex hormones and inflammation factors.The contents of malondialdehyde (MDA), H2O2, NAD+/NADH and ATP in the testicular tissues were tested with corresponding reagent kits.Western blotting was utilized to detect protein levels of β-gal, p16, and GR in testicular tissue, and transmission electron microscopy was used to observe mitochondrial structure of spermatogenic cells. Results Compared with the DMSO group, the sperm density, serum levels of testosterone (T), luteinizing hormone (LH) and follicle stimulating hormone (FSH) were decreased while those of CORT and estradiol (E2) were increased in the CUMS group (all P < 0.001).Serum pro-inflammatory factors IL-6 and TNF-α concentrations were increased while anti-inflammatory factor IL-10 concentration was decreased in the CUMS group than the DMSO group (all P < 0.05).And, ATP content and NAD+/NADH ratio were decreased while MDA and H2O2 levels were elevated in testicular tissues in the CUMS group (all P < 0.05).Moreover, the protein levels of testicular cell aging markers β-gal, p16 and GR were significantly enhanced in the CUMS group (all P < 0.01), accompanied by swelling and vacuolization of mitochondrial structures in spermatogenic cells.RU486 treatment effectively improved sperm density and increased CORT level and down-regulated the testicular β-gal, p16 and GR protein level (all P < 0.05). Conclusion Chronic psychological stress induces testicular damage in rats, presenting declines in sperm density and CORT level, which is possibly associated with GR-mediated cell senescence.